Urosolenia and Acanthoceras species from Hainan Province, China - Liu, Yan; Kociolek, John Patrick; Fan, Yawen (Phytotaxa, 2016)
Urosolenia and Acanthoceras are reported as cosmopolitan centric genera, but records of these two taxa are infrequent. During an investigation of the diatom flora from Hainan Province, South of China, three Urosolenia and one Acanthoceras species were observed. Based on the morphological and ultrastructural features, we propose these three Urosolenia species as new to Science, named as U. yalongii sp. nov., U. truncata sp. nov. and U. subtenuis sp. nov. Urosolenia yalongii differs from other species such as U. amazonica, U. delicatissima and U. eriensis by its lower density of cingula, and the presence of elongated poroids on the valve and 3–5 teeth on the end of extension. Urosolenia truncata is similar to U. yalongii but it has denser cingula and the blunt ends of the extension make it very distinctive from other known species of the genus. Urosolenia subtenuis can be separated from all other Urosolenia species by its small frustule, lower density of bands and by having 2–3 teeth with a ligula on the tip of the extension. Additionally, one taxon of Acanthoceras resembling A. zachariasii was observed; the Hainan specimens differ from previous descriptions of A. zachariasii by presenting a lower density of cingula and 5–7 teeth at the tip of the extension. Lack of information on the type of this species suggests to avoid determining the Hainan specimens as a separate species.